A sensitive method for the rapid determination of underivatized ethyl carbamate in fortified wine by liquid chromatography-electrospray tandem mass spectrometry - Leça, João M. (2021)
This work presents the optimization of a miniaturized liquid-liquid extraction (mLLE) followed by reversed-phase liquid chromatography-electrospray tandem mass spectrometry (RP-HPLC-MS/MS) for the determination of ethyl carbamate (EC) in fortified wine, without using derivatizing agents. The mLLE was optimized by an experimental design. Thus, 15 mL of wine and 8 mL of ethyl acetate were used for the extraction. After concentration, each extract was injected into the HPLC MS/MS equipment and the characteristic secondary ion transition of EC (m/z = 90.10 → 62.05) was used for the quan tification purposes. The proposed method presented a good lin earity (R2 = 0.9999) and a high sensitivity with low limits of detection (LOD) and quantification (LOQ), 0.17 and 0.52 μg L−1 , respectively. The precision (repeatability and reproducibility) never exceeded 8% of variation, and the recoveries varied between 93 and 114%. The applicability of the method was checked through the analysis of 24 fortified wines, with EC values ranging between 23 ± 1 and 194 ± 5 μg L−1 . All chromatograms revealed good peak resolutions. This new method is efficient for the simple, fast, and reliable determination of EC in fortified wines, providing great sensitivity without using derivatizing agents or large volumes of organic solvents.